Assessing the Impact of Tourism on the Physical Environment of a Small Coastal Town: Girne, Northern Cyprus - Vehbi, Beser Oktay; Doratli, Naciye (Routledge Journals, Taylor & Francis Ltd, 2010)
The aim of this paper is to assess the impact of tourism on Girne, with special emphasis on the natural and built environments. With this aim in mind, the study first reviews the positive and negative impacts of tourism on the physical environment of the coastal cities. These impacts are used to develop the methodology for assessing the impacts in the second part. Accordingly, 11 negative impacts/indicators (4 for natural environment and 7 for built environment) and 9 positive impacts/indicators (3 for natural environment and 6 for built environment) have been selected and founded as relevant for assessing tourism impacts of the case study. Then, each selected indicator has been measured by using a series of analyses results. Following these results, some suggestions are made for encouraging the positive impacts and for decreasing the pressure created by tourism on the physical environment of the town. The issues discussed in the paper are relevant to other small historic cities in the Mediterranean Basin. The paper concludes by emphasizing the need for proper planning strategies to minimize negative impacts on physical environment and significant difference of impacts between historic district and newly developing areas.
Keywords: Attitudes